Students’ Algebraic Thinking Skills Through Creative Problem Solving Learning Models - Anggraini, Wita; Pratiwi, Weni Dwi (SJME (Supremum Journal of Mathematics Education), 2024)
This research aims to describe algebraic thinking skills in two-variable linear equation systems material through the steps of the Creative Problem Solving learning (CPS) learning model using worksheets. The research subjects were students of SMP Negeri 02 Sembawa class VIII-7 in the 2023/2024 academic year. The type of research is descriptive qualitative. The data collection techniques are written tests and interviews. Indicators of algebraic thinking skills include indicators at generational, transformational and meta-global level activities. After implementing CPS in learning, the test results showed that the percentage of students' algebraic thinking skills for generational activities in question number one was 48% and number two was 89%. For transformational activities, the percentage of students who were able to achieve them was 38% for number one and 38% for number two. Meanwhile, for meta-global level activities, the percentage of students who were able to achieve them was 45% for number one and 82% for number two. It can be concluded that the indicators of algebraic thinking skills that appear most frequently are in generational activities.